The age of football : the global game in the twenty-first centuary - Goldblatt, David, 1930- (Macmillan, 2019)
The epic exploration of football in the twenty-first century through the prism of sociology, politics, and economics, by David Goldblatt, the critically acclaimed author of The Ball is Round.